From Ecuador to Elsewhere: The (Re)Configuration of a Transit Country. Issue 1 (1st June 2020) - Álvarez Velasco, Soledad
Abstract: Unlike other transit countries, Ecuador's position as a transit country has just begun to be publicly addressed, having been more of a strategic public secret than a topic of public interest. Based on 12 months of ethnographic fieldwork conducted between 2015 and 2016, this article discusses the dynamics of the (re)configuration of Ecuador as a transit country used by both immigrants and Ecuadorean deportees mainly from the United States to reach other destinations. It argues that this process should be interpreted in light of a series of historical and political elements in tension. The article suggests that the subtle presence of the United States' externalized border, together with national political inconsistencies, have a repressive as well as a productive effect, which has functioned to produce a systemic form of selective control of transit mobility.